2016
DOI: 10.3802/jgo.2016.27.e62
|View full text |Cite
|
Sign up to set email alerts
|

Distal pancreatectomy with splenectomy for the management of splenic hilum metastasis in cytoreductive surgery of epithelial ovarian cancer

Abstract: ObjectiveDistal pancreatectomy with splenectomy may be required for optimal cytoreductive surgery in patients with epithelial ovarian cancer (EOC) metastasized to splenic hilum. This study evaluates the morbidity and treatment outcomes of the uncommon procedure in the management of advanced or recurrent EOC.MethodsThis study recruited 18 patients who underwent distal pancreatectomy with splenectomy during cytoreductive surgery of EOC. Their clinicopathological characteristics and follow-up data were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
14
2
2
Order By: Relevance
“…However, splenectomy as a part of cytoreductive surgery in EOC demonstrating splenic metastasis is rarely seen in clinical practice. 7 , 8 There are two reasons for this phenomenon. First, many studies suggest that the splenic capsule could act as a shield and its contractile properties might also be involved by squeezing the tumor cells out.…”
Section: Discussionmentioning
confidence: 99%
“…However, splenectomy as a part of cytoreductive surgery in EOC demonstrating splenic metastasis is rarely seen in clinical practice. 7 , 8 There are two reasons for this phenomenon. First, many studies suggest that the splenic capsule could act as a shield and its contractile properties might also be involved by squeezing the tumor cells out.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that there is significant morbidity of postoperative patients, but it was found that the vast majority of complications could be treated conservatively, with no need for surgical reintervention [39].…”
Section: • Interval Citoreductionmentioning
confidence: 99%
“…It is well accepted that optimal cytoreduction improves survival in ovarian cancer patients [3,4] . In some circumstances, removal of the spleen as part of upper abdominal surgery is required to achieve complete resection [5,6] .…”
Section: Introductionmentioning
confidence: 99%